ACCOUNTING THE COLLECTIVE ENVIRONMRENT MOTION IN THE MODIFIED LATTICE BOLTZMANN EQUATIONS METHOD - Глазок, О.М. (Science-based technologies, 2014)
It is proposed to take into account influence of collective motion in the modified method of the Boltzmann lattice equations by introduction of two additional stages of calculation. On the stage of modeling of collective motion of matter, the whole cell moves in the direction of the collective speed vector. As the group of particles occupies new position, they are distributed on cells taking into account their speeds distributions. It is further necessary to execute the additional step of relaxation, during which to account the matter which is on territory of every cell after the step of collective motion modeling, and to define the integral statistical distributions of speeds for every cell. At the same time, collective motion can also be taken into account in the functions of distribution on the stage of classic «static» transfer. It is suggested to enter in a model a parameter which will link the degree of account of collective motion in these two stages. Possibility of accounting of influence of temperature on the process of matter exchange is considered.